2014
DOI: 10.3109/02656736.2014.966790
|View full text |Cite
|
Sign up to set email alerts
|

Eradicating group A streptococcus bacteria and biofilms using functionalised multi-wall carbon nanotubes

Abstract: The results of this study support the premise that carbon nanotubes may be effectively utilised as highly localised photothermal agents with the potential for translation into the clinical treatment of bacterial infections of soft tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“… 10 We and others have instead explored the use of PT therapy using strong light absorbers such as gold (Au) nanoparticles or carbon nanotubes to generate laser-induced PT effects capable of the targeted physical destruction of bacterial cells. 11 13 Using a murine model, we confirmed that this approach can be combined with photoacoustic flow cytometry to detect and eradicate bacterial cells in the blood. 14 , 15 Although PT killing alone has great potential to treat bacteremia and has shown some potential in the context of a biofilm, 13 the combined use of PT killing with controlled antibiotic release has the potential to dramatically improve treatment efficacy compared to either therapeutic approach alone.…”
mentioning
confidence: 56%
“… 10 We and others have instead explored the use of PT therapy using strong light absorbers such as gold (Au) nanoparticles or carbon nanotubes to generate laser-induced PT effects capable of the targeted physical destruction of bacterial cells. 11 13 Using a murine model, we confirmed that this approach can be combined with photoacoustic flow cytometry to detect and eradicate bacterial cells in the blood. 14 , 15 Although PT killing alone has great potential to treat bacteremia and has shown some potential in the context of a biofilm, 13 the combined use of PT killing with controlled antibiotic release has the potential to dramatically improve treatment efficacy compared to either therapeutic approach alone.…”
mentioning
confidence: 56%
“…It is important to note that this technique is different from the more traditional photothermal killing of bacteria, where the combined use of AuNP and laser irradiation kills bacteria by producing heat 31 , 47 , 48 . Despite numerous in vitro studies reporting the effective eradication of biofilms by photothermal treatment 49 54 , translation into clinical practice may be difficult because of heat diffusion into the surrounding healthy tissue 31 , 51 . One study reported on the destruction of Bacillus subtilis biofilms grown on a gold-coated substrate following pulsed laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In fact, numerous kinds of antibacterial materials and strategies have been developed in the past decades. For example, chemotherapies using antibacterial polypeptides, 10 noble metal nanoparticles (NPs), 11,12 semiconductor NPs 13,14 and carbon-based nanomaterials (CNMs) 15,16 were all proved to exhibit antimicrobial activities. More recently, photothermal or photodynamic sterilization techniques were extensively investigated in the eradication of bacteria via production of massive heating or the generation of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%